Thermoplastic resin composition and molded article composed of the same

The thermoplastic resin composition, formulated with fatty acid polyester resin and phosphonic acid esters, addresses the challenges of thermal stability and recyclability, achieving excellent mold release, reduced strength loss, and enhanced recyclability for demanding applications.

JP2025065611APending Publication Date: 2025-04-22TEIJIN LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023174916
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-10
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

Existing thermoplastic resin compositions face challenges with insufficient thermal stability during molding, particularly under high-temperature conditions, and lack excellent recyclability while maintaining strength and mold release properties.

Method used

A thermoplastic resin composition is developed by blending a fatty acid polyester resin with specific alcohol components and phosphonic acid esters, which enhances mold release properties, reduces strength loss, and improves recyclability even under harsh processing conditions.

Benefits of technology

The composition achieves excellent mold release properties, low strength reduction, and high recyclability, making it suitable for applications requiring thin and lightweight structures, and ensuring performance stability even after recycling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025065611000009
    Figure 2025065611000009
  • Figure 2025065611000010
    Figure 2025065611000010
  • Figure 2025065611000001
    Figure 2025065611000001
Patent Text Reader

Abstract

To provide a thermoplastic resin composition having excellent releasability, little deterioration in strength and excellent recyclability even under severe processing conditions and a molded article composed thereof.SOLUTION: There is provided a thermoplastic resin composition which comprises (B) 0.01 to 1 pt.wt.of a fatty acid polyester resin (B component) containing a constituent unit derived from at least one alcohol selected from the group consisting of 1-docosanol and 1-octacosanol and 0.001 to 1 pt.wt. of at least one phosphoric acid ester (C component) selected from the group consisting of a phosphonic acid ester (C-1 component) having an acid value of 0.01 to 0.30 mg KOH / g, an acidic phosphoric acid ester (C-2 component) having an acid value of 10 to 200 mg KOH / g and a trialkyl phosphate (C-3 component) based on (A) 100 pts.wt. of a thermoplastic resin (A component).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thermoplastic resin composition which has excellent mold releasability, little loss in strength, and excellent recyclability even under severe processing conditions, and to a molded article made from the same. [Background technology]

[0002] Thermoplastic resin compositions are used in a wide range of fields, such as housings and parts for electric / electronic / OA devices, interior / exterior parts for automobiles, furniture, musical instruments, and miscellaneous goods. In particular, in recent years, high recyclability of thermoplastic resin compositions is desired in order to realize a sustainable society. On the other hand, it is widely known to use phosphorus-based compounds as heat stabilizers in thermoplastic resin compositions. Patent Document 1 discloses the addition of a specific phosphorus-based compound to a resin component consisting of a polycarbonate resin and a polyester resin. Patent Document 2 discloses the use of a phosphorus-based compound in combination. However, the thermal stability during molding processing is still insufficient in existing methods, and in particular in applications requiring thin-walled and lightweight products, the molding conditions tend to be high temperatures, and there are an increasing number of cases where the thermal stability is insufficient. Furthermore, there is a high demand for products to be recycled and used again, and there is an increasing need to propose materials that can satisfy the demand for thermoplastic resin compositions that do not lose strength even under harsh processing conditions and have excellent recyclability. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent No. 4983427 [Patent Document 2] Patent No. 5640734 Summary of the Invention [Problem to be solved by the invention]

[0004] An object of the present invention is to provide a thermoplastic resin composition which has excellent mold releasability, little loss in strength and excellent recyclability even under severe processing conditions, and a molded article made from the same. [Means for solving the problem]

[0005] As a result of intensive research to solve these problems, the inventors have discovered that by blending a fatty acid polyester resin having a specific alcohol component and a phosphonic acid ester or an acidic phosphate ester having a specific acid value into a thermoplastic resin, it is possible to provide a thermoplastic resin composition that has excellent release properties, little strength reduction, and excellent recyclability even under harsh processing conditions, and a molded article made from the same, and have arrived at the present invention.

[0006] That is, the present invention is as follows. 1. A thermoplastic resin composition comprising, per 100 parts by weight of (A) a thermoplastic resin (component A), 0.01 to 1 part by weight of (B) a fatty acid polyester resin (component B) containing a structural unit derived from at least one alcohol selected from the group consisting of 1-docosanol and 1-octacosanol, and (C) 0.001 to 1 part by weight of at least one phosphoric acid ester (component C) selected from the group consisting of a phosphonic acid ester (component C-1) having an acid value of 0.01 to 0.30 mg KOH / g, an acidic phosphoric acid ester (component C-2) having an acid value of 10 to 200 mg KOH / g, and a trialkyl phosphate (component C-3). 2. The thermoplastic resin composition according to item 1 above, wherein component A is at least one thermoplastic resin selected from the group consisting of (A-1) polycarbonate resin (component A-1), (A-2) ABS resin (component A-2), (A-3) polyester resin excluding component B (component A-3), (A-4) AS resin (component A-4), (A-5) PS resin (component A-5) and (A-6) AAS resin (component A-6). 3. The thermoplastic resin composition according to item 1 or 2 above, wherein component C is triethylphosphonoacetate. 4. A thermoplastic resin composition according to claim 1 or 2, wherein component C is trimethyl phosphate. 5. The thermoplastic resin composition according to any one of the preceding items 1 to 4, wherein the acid value of component B is 50 mgKOH / g or less. 6. A molded article obtained by molding the thermoplastic resin composition according to any one of the preceding items 1 to 5.

[0007] Hereinafter, the present invention will be specifically described.

[0008] <Component A: Thermoplastic resin composition> The thermoplastic resin used as component A of the present invention is preferably a polycarbonate resin, an ABS resin, a polyester resin excluding component B, an AS resin, a PS resin, an AAS resin, an AES resin, a polyamide resin, a polyolefin resin, a fluororesin, a PPS resin, a PEEK resin, a polyarylate resin, a polyacetal resin, etc., and more preferably at least one thermoplastic resin selected from the group consisting of a polycarbonate resin, an ABS resin, a polyester resin excluding component B, an AS resin, a PS resin, and an AAS resin.

[0009] <Component A-1: Polycarbonate resin> The polycarbonate resin used as component A-1 of the present invention is obtained by reacting a dihydric phenol with a carbonate precursor. Examples of the reaction method include an interfacial polymerization method, a melt transesterification method, a solid-phase transesterification method of a carbonate prepolymer, and a ring-opening polymerization method of a cyclic carbonate compound.

[0010] Representative examples of the dihydric phenols used herein include hydroquinone, resorcinol, 4,4'-biphenol, 1,1-bis(4-hydroxyphenyl)ethane, 2,2-bis(4-hydroxyphenyl)propane (commonly known as bisphenol A), 2,2-bis(4-hydroxy-3-methylphenyl)propane, 2,2-bis(4-hydroxyphenyl)butane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 2,2-bis(4-hydroxyphenyl)pentane, 4,4'-(p-phenylene) Examples of the dihydric phenol include 4,4'-(m-phenylenediisopropylidene)diphenol, 1,1-bis(4-hydroxyphenyl)-4-isopropylcyclohexane, bis(4-hydroxyphenyl)oxide, bis(4-hydroxyphenyl)sulfide, bis(4-hydroxyphenyl)sulfoxide, bis(4-hydroxyphenyl)sulfone, bis(4-hydroxyphenyl)ketone, bis(4-hydroxyphenyl)ester, bis(4-hydroxy-3-methylphenyl)sulfide, 9,9-bis(4-hydroxyphenyl)fluorene, and 9,9-bis(4-hydroxy-3-methylphenyl)fluorene. The preferred dihydric phenol is a bis(4-hydroxyphenyl)alkane, and among them, bisphenol A is particularly preferred from the viewpoint of impact resistance and is widely used.

[0011] In the present invention, in addition to the bisphenol A-based polycarbonate resin, which is a general-purpose polycarbonate resin, it is possible to use special polycarbonate resins produced using other dihydric phenols as the A-1 component. For example, polycarbonate resins (homopolymers or copolymers) using 4,4'-(m-phenylenediisopropylidene)diphenol (hereinafter sometimes abbreviated as "BPM"), 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane (hereinafter sometimes abbreviated as "Bis-TMC"), 9,9-bis(4-hydroxyphenyl)fluorene, and 9,9-bis(4-hydroxy-3-methylphenyl)fluorene (hereinafter sometimes abbreviated as "BCF") as part or all of the dihydric phenol component are suitable for applications in which dimensional changes due to water absorption and dimensional stability are particularly demanding. The dihydric phenol other than BPA is preferably used in an amount of 5 mol % or more, particularly 10 mol % or more, of the total dihydric phenol components constituting the polycarbonate resin. In particular, when high rigidity and better hydrolysis resistance are required, it is particularly suitable that the component A constituting the resin composition is a copolymer polycarbonate resin of the following (1) to (3). (1) A copolymerized polycarbonate resin in which, relative to 100 mol % of a dihydric phenol component constituting the polycarbonate resin, BPM is 20 to 80 mol % (more preferably 40 to 75 mol %, and even more preferably 45 to 65 mol %) and BCF is 20 to 80 mol % (more preferably 25 to 60 mol %, and even more preferably 35 to 55 mol %). (2) A copolymerized polycarbonate resin in which, relative to 100 mol % of a dihydric phenol component constituting the polycarbonate resin, BPA is 10 to 95 mol % (more preferably 50 to 90 mol %, and even more preferably 60 to 85 mol %) and BCF is 5 to 90 mol % (more preferably 10 to 50 mol %, and even more preferably 15 to 40 mol %). (3) A copolymer polycarbonate resin in which, relative to 100 mol % of the dihydric phenol component constituting the polycarbonate resin, BPM is 20 to 80 mol % (more preferably 40 to 75 mol %, and even more preferably 45 to 65 mol %) and Bis-TMC is 20 to 80 mol % (more preferably 25 to 60 mol %, and even more preferably 35 to 55 mol %).

[0012] These special polycarbonate resins may be used alone or in a suitable mixture of two or more. They may also be used in a mixture with the commonly used bisphenol A polycarbonate resin. The production methods and properties of these special polycarbonate resins are described in detail in, for example, JP-A-6-172508, JP-A-8-27370, JP-A-2001-55435, and JP-A-2002-117580.

[0013] Among the various polycarbonate resins mentioned above, those in which the copolymer composition and the like are adjusted to bring the water absorption rate and Tg (glass transition temperature) into the ranges described below have good hydrolysis resistance of the polymer itself and are also remarkably excellent in terms of low warpage after molding, and are therefore particularly suitable in fields where dimensional stability is required. (i) a polycarbonate resin having a water absorption rate of 0.05 to 0.15%, preferably 0.06 to 0.13%, and a Tg of 120 to 180° C.; or (ii) A polycarbonate resin having a Tg of 160 to 250° C., preferably 170 to 230° C., and a water absorption of 0.10 to 0.30%, preferably 0.13 to 0.30%, and more preferably 0.14 to 0.27%.

[0014] Here, the water absorption rate of the polycarbonate resin is a value measured by using a disk-shaped test piece having a diameter of 45 mm and a thickness of 3.0 mm and immersing it in water at 23°C for 24 hours in accordance with ISO62-1980, and measuring the moisture content. Also, Tg (glass transition temperature) is a value determined by differential scanning calorimetry (DSC) measurement in accordance with JIS K7121.

[0015] The carbonate precursor may be a carbonyl halide, a carbonic acid diester or a haloformate, and specific examples thereof include phosgene, diphenyl carbonate or a dihaloformate of a dihydric phenol.

[0016] When the dihydric phenol and carbonate precursor are used to produce a polycarbonate resin by interfacial polymerization, a catalyst, a terminal terminator, an antioxidant for preventing oxidation of the dihydric phenol, etc. may be used as necessary. The polycarbonate resin of the present invention includes a branched polycarbonate resin copolymerized with a trifunctional or higher polyfunctional aromatic compound, a polyester carbonate resin copolymerized with an aromatic or aliphatic (including alicyclic) bifunctional carboxylic acid, a copolymerized polycarbonate resin copolymerized with a bifunctional alcohol (including alicyclic), and a polyester carbonate resin copolymerized with such a bifunctional carboxylic acid and a bifunctional alcohol. The polycarbonate resin may also be a mixture of two or more of the obtained polycarbonate resins.

[0017] The branched polycarbonate resin can impart drip prevention properties and the like to the thermoplastic resin composition of the present invention. Examples of trifunctional or higher polyfunctional aromatic compounds used in such branched polycarbonate resins include phloroglucin, phloroglucide, 4,6-dimethyl-2,4,6-tris(4-hydroxyphenyl)heptene-2,2,4,6-trimethyl-2,4,6-tris(4-hydroxyphenyl)heptane, 1,3,5-tris(4-hydroxyphenyl)benzene, 1,1,1-tris(4-hydroxyphenyl)ethane, 1,1,1-tris(3,5-dimethyl-4-hydroxyphenyl)ethane, 2,6-bis(2-hydroxy-5-methylbenzyl)-4-methylphenol, 4-{4-[1,1-bis(4- Examples of the trisphenols include trisphenols such as 1,4-dimethylbenzylphenol, tetra(4-hydroxyphenyl)methane, bis(2,4-dihydroxyphenyl)ketone, 1,4-bis(4,4-dihydroxytriphenylmethyl)benzene, trimellitic acid, pyromellitic acid, benzophenonetetracarboxylic acid, and acid chlorides thereof. Among these, 1,1,1-tris(4-hydroxyphenyl)ethane and 1,1,1-tris(3,5-dimethyl-4-hydroxyphenyl)ethane are preferred, and 1,1,1-tris(4-hydroxyphenyl)ethane is particularly preferred.

[0018] The structural unit derived from a polyfunctional aromatic compound in the branched polycarbonate resin is preferably 0.01 to 1 mol%, more preferably 0.05 to 0.9 mol%, and even more preferably 0.05 to 0.8 mol% out of the total 100 mol% of the structural unit derived from a dihydric phenol and the structural unit derived from the polyfunctional aromatic compound. In particular, in the case of the melt transesterification method, a branched structural unit may be generated as a side reaction, and the amount of such a branched structural unit is preferably 0.001 to 1 mol%, more preferably 0.005 to 0.9 mol%, and even more preferably 0.01 to 0.8 mol% out of the total 100 mol% of the structural unit derived from the dihydric phenol. The proportion of such a branched structure is 1 It can be calculated by H-NMR measurement.

[0019] The aliphatic difunctional carboxylic acid is preferably an α,ω-dicarboxylic acid. Examples of the aliphatic difunctional carboxylic acid include linear saturated aliphatic dicarboxylic acids such as sebacic acid (decanedioic acid), dodecanedioic acid, tetradecanedioic acid, octadecanedioic acid, and icosane diacid, and alicyclic dicarboxylic acids such as cyclohexane dicarboxylic acid. The bifunctional alcohol is more preferably an alicyclic diol, such as cyclohexane dimethanol, cyclohexane diol, and tricyclodecane dimethanol.

[0020] The reaction modes of the method for producing the polycarbonate resin of the present invention, such as the interfacial polymerization method, the melt transesterification method, the carbonate prepolymer solid-phase transesterification method, and the ring-opening polymerization method of a cyclic carbonate compound, are well known in various literatures and patent publications.

[0021] In producing the thermoplastic resin composition of the present invention, the viscosity average molecular weight of the polycarbonate resin is preferably 12,500 to 32,000, more preferably 16,000 to 28,000, and further preferably 18,000 to 26,000. With a polycarbonate resin having a viscosity average molecular weight of less than 12,500, good mechanical properties may not be obtained. On the other hand, a resin composition obtained from a polycarbonate resin having a viscosity average molecular weight of more than 32,000 may have poor moldability.

[0022] The viscosity average molecular weight in the present invention is calculated by the specific viscosity (η SP ) was measured at 20°C using an Ostwald viscometer from a solution of 0.7 g of polycarbonate dissolved in 100 ml of methylene chloride. Specific viscosity (η SP )=(t-t0) / t0 [t0 is the number of seconds that methylene chloride falls, and t is the number of seconds that the sample solution falls] The specific viscosity (η SP ) and calculate the viscosity average molecular weight M using the following formula: η SP / c=[η]+0.45×[η] 2 c (where [η] is the intrinsic viscosity) [η]=1.23×10 -4 M 0.83 c=0.7

[0023] The viscosity average molecular weight of the polycarbonate resin in the thermoplastic resin composition of the present invention is calculated as follows. That is, the composition is mixed with methylene chloride in an amount 20 to 30 times by weight, and the soluble matter in the composition is dissolved. The soluble matter is collected by filtration through Celite. The solvent in the resulting solution is then removed. The solid after the solvent removal is thoroughly dried to obtain a solid of components that dissolve in methylene chloride. 0.7 g of the solid is dissolved in 100 ml of methylene chloride, and the specific viscosity at 20°C is determined in the same manner as above, and the viscosity average molecular weight M is calculated from the specific viscosity in the same manner as above.

[0024] The polycarbonate resin of the present invention may be a polycarbonate-polydiorganosiloxane copolymer resin. The polycarbonate-polydiorganosiloxane copolymer resin is preferably a copolymer resin prepared by copolymerizing a dihydric phenol represented by the following general formula (1) and a hydroxyaryl-terminated polydiorganosiloxane represented by the following general formula (3).

[0025] [ka]

[0026] [In the above general formula (1), R 1 and R 2each independently represents a group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 18 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 14 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxy group, and when there are a plurality of each, they may be the same or different, e and f each represent an integer of 1 to 4, and W represents a single bond or at least one group selected from the group consisting of groups represented by the following general formula (2):

[0027] [ka]

[0028] [In the above general formula (2), R 11 ,R 12 ,R 13 ,R 14 ,R 15 ,R 16 ,R 17 and R 18 each independently represents a group selected from the group consisting of a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, an aryl group having 6 to 14 carbon atoms, and an aralkyl group having 7 to 20 carbon atoms; R 19 and R 20 each independently represents a group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 10 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxy group, and when there are a plurality of groups, they may be the same or different, g is an integer from 1 to 10, and h is an integer from 4 to 7.

[0029] [ka]

[0030] [In the above general formula (3), R 3 , R 4 , R 5 , R 6 , R 7 and R 8 are each independently a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 12 carbon atoms; R 9 and R 10 are each independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms, p is a natural number, q is 0 or a natural number, and p+q is a natural number of 4 or more and 350 or less, and X is a divalent aliphatic group having 2 to 8 carbon atoms.]

[0031] Examples of the dihydric phenol (I) represented by the general formula (1) include 4,4'-dihydroxybiphenyl, bis(4-hydroxyphenyl)methane, 1,1-bis(4-hydroxyphenyl)ethane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 2,2-bis(4-hydroxy-3,3'-biphenyl)propane, 2,2- Bis(4-hydroxy-3-isopropylphenyl)propane, 2,2-bis(3-t-butyl-4-hydroxyphenyl)propane, 2,2-bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxyphenyl)octane, 2,2-bis(3-bromo-4-hydroxyphenyl)propane, 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane, 2,2-bis(3-cyclohexyl-4-hydroxyphenyl)propane, 1,1-bis(3-cyclohexyl-4-hydroxyphenyl)cyclohexane, bis(4-hydroxyphenyl)propane, 4,4'-dihydroxydiphenylmethane, 9,9-bis(4-hydroxyphenyl)fluorene, 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)cyclopentane, 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxy-3,3'-dimethyldiphenyl ether, 4,4'-sulfonyldiphenol, 4,4'-dihydroxydiphenyl sulfoxide, 4,4'-dihydroxydiphenyl sulfide, 2,2'- Dimethyl-4,4'-sulfonyldiphenol, 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfoxide, 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfide, 2,2'-diphenyl-4,4'-sulfonyldiphenol, 4,4'-dihydroxy-3,3'-diphenyldiphenyl sulfoxide, 4,4'-dihydroxy-3,3'-diphenyldiphenyl sulfide, 1,3-bis{2-(4-hydroxyphenyl)propyl}benzene, 1,4-bis{2-(4-hydroxyphenyl)propyl}benzene, 1,Examples of the cyclohexane derivatives include 4-bis(4-hydroxyphenyl)cyclohexane, 1,3-bis(4-hydroxyphenyl)cyclohexane, 4,8-bis(4-hydroxyphenyl)tricyclo[5.2.1.02,6]decane, 4,4'-(1,3-adamantanediyl)diphenol, and 1,3-bis(4-hydroxyphenyl)-5,7-dimethyladamantane.

[0032] Among these, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 4,4'-sulfonyldiphenol, 2,2'-dimethyl-4,4'-sulfonyldiphenol, 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, 1,3-bis{2-(4-hydroxyphenyl)propyl}benzene, and 1,4-bis{2-(4-hydroxyphenyl)propyl}benzene are preferred, and 2,2-bis(4-hydroxyphenyl)propane, 1,1-bis(4-hydroxyphenyl)cyclohexane (BPZ), 4,4'-sulfonyldiphenol, and 9,9-bis(4-hydroxy-3-methylphenyl)fluorene are particularly preferred. Among these, 2,2-bis(4-hydroxyphenyl)propane, which has excellent strength and good durability, is most suitable. These may be used alone or in combination of two or more kinds.

[0033] As the hydroxyaryl-terminated polydiorganosiloxane represented by the above general formula (3), for example, the compounds shown below are suitably used.

[0034] [ka]

[0035] Hydroxyaryl-terminated polydiorganosiloxane (II) is easily produced by hydrosilylation reaction of phenols having an olefinic unsaturated carbon-carbon bond, preferably vinylphenol, 2-allylphenol, isopropenylphenol, or 2-methoxy-4-allylphenol, with the end of a polysiloxane chain having a predetermined degree of polymerization. Among them, (2-allylphenol)-terminated polydiorganosiloxane and (2-methoxy-4-allylphenol)-terminated polydiorganosiloxane are preferred, and (2-allylphenol)-terminated polydimethylsiloxane and (2-methoxy-4-allylphenol)-terminated polydimethylsiloxane are particularly preferred. The molecular weight distribution (Mw / Mn) of the hydroxyaryl-terminated polydiorganosiloxane (II) is preferably 3 or less. In order to achieve even better low outgassing properties during high-temperature molding and low-temperature impact properties, the molecular weight distribution (Mw / Mn) is more preferably 2.5 or less, and even more preferably 2 or less. If the upper limit of this preferred range is exceeded, the amount of outgassing during high-temperature molding will be large, and low-temperature impact resistance may be poor.

[0036] In order to achieve a high level of impact resistance, the diorganosiloxane polymerization degree (p+q) of the hydroxyaryl-terminated polydiorganosiloxane (II) is preferably 10 to 300. The diorganosiloxane polymerization degree (p+q) is more preferably 10 to 200, further preferably 12 to 150, and particularly preferably 14 to 100. Below the lower limit of this preferred range, the impact resistance that is a characteristic of the polycarbonate-polydiorganosiloxane copolymer is not effectively exhibited, while above the upper limit of this preferred range, poor appearance appears.

[0037] The polydiorganosiloxane content in the total weight of the polycarbonate-polydiorganosiloxane copolymer resin used in component A-1 is preferably 0.1 to 50% by weight. The polydiorganosiloxane content is more preferably 0.5 to 30% by weight, and even more preferably 1 to 20% by weight. At or above the lower limit of this preferred range, excellent impact resistance and flame retardancy are obtained, while at or below the upper limit of this preferred range, a stable appearance that is not easily affected by molding conditions is easily obtained. The polydiorganosiloxane polymerization degree and polydiorganosiloxane content are, 1 It can be calculated by H-NMR measurement.

[0038] In the present invention, the hydroxyaryl-terminated polydiorganosiloxane (II) may be used alone or in combination of two or more kinds. In addition, comonomers other than the dihydric phenol (I) and hydroxyaryl-terminated polydiorganosiloxane (II) may be used in an amount of up to 10% by weight based on the total weight of the copolymer, provided that the use does not interfere with the present invention.

[0039] In the present invention, a mixed solution containing an oligomer having a terminal chloroformate group is prepared in advance by reacting a dihydric phenol (I) with a carbonate-forming compound in a mixed solution of a water-insoluble organic solvent and an aqueous alkaline solution.

[0040] In producing an oligomer of the dihydric phenol (I), the entire amount of the dihydric phenol (I) used in the method of the present invention may be converted into an oligomer at once, or a part of it may be added as a post-added monomer as a reaction raw material to the interfacial polycondensation reaction in the latter stage. The post-added monomer is added to quickly advance the polycondensation reaction in the latter stage, and there is no need to add it if it is not necessary. The method of this oligomer formation reaction is not particularly limited, but it is usually preferable to carry out the reaction in a solvent in the presence of an acid binder.

[0041] The proportion of the carbonate ester-forming compound used may be appropriately adjusted in consideration of the stoichiometric ratio (equivalent) of the reaction. When a gaseous carbonate ester-forming compound such as phosgene is used, it is preferable to employ a method of blowing the gaseous compound into the reaction system.

[0042] As the acid binder, for example, an alkali metal hydroxide such as sodium hydroxide or potassium hydroxide, an alkali metal carbonate such as sodium carbonate or potassium carbonate, an organic base such as pyridine, or a mixture thereof can be used. The proportion of the acid binder used can be appropriately determined in consideration of the stoichiometric ratio (equivalent) of the reaction, as described above. Specifically, it is preferable to use 2 equivalents or a slightly excess amount of the acid binder relative to the number of moles of the dihydric phenol (I) used to form the oligomer (usually 1 mole corresponds to 2 equivalents).

[0043] As the solvent, a solvent inert to various reactions, such as those used in the production of known polycarbonates, may be used alone or as a mixed solvent. Representative examples include hydrocarbon solvents such as xylene, and halogenated hydrocarbon solvents such as methylene chloride and chlorobenzene. In particular, halogenated hydrocarbon solvents such as methylene chloride are preferably used.

[0044] The reaction pressure for oligomer formation is not particularly limited, and may be normal pressure, elevated pressure, or reduced pressure, but it is usually advantageous to carry out the reaction under normal pressure. The reaction temperature is selected from the range of -20 to 50°C, and since heat is generated during polymerization in many cases, it is desirable to cool the reaction with water or ice. The reaction time depends on other conditions and cannot be generally specified, but is usually carried out for 0.2 to 10 hours. The pH range for the oligomer formation reaction is the same as that of known interfacial reaction conditions, and the pH is always adjusted to 10 or higher.

[0045] In the present invention, after obtaining a mixed solution containing an oligomer of dihydric phenol (I) having terminal chloroformate groups in this manner, the mixed solution is stirred while adding hydroxyaryl-terminated polydiorganosiloxane (II) represented by general formula (3) that has been highly refined to a molecular weight distribution (Mw / Mn) of 3 or less to the dihydric phenol (I), and the hydroxyaryl-terminated polydiorganosiloxane (II) and the oligomer are subjected to interfacial polycondensation to obtain a polycarbonate-polydiorganosiloxane copolymer.

[0046] [ka]

[0047] (In the above general formula (3), R 3 , R 4 , R 5 , R 6 , R 7 and R 8 are each independently a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 12 carbon atoms; R 9 and R 10 are each independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms, p is a natural number, q is 0 or a natural number, and p+q is a natural number of 4 or more and 350 or less, and X is a divalent aliphatic group having 2 to 8 carbon atoms.

[0048] In carrying out the interfacial polycondensation reaction, an acid binder may be appropriately added in consideration of the stoichiometric ratio (equivalent) of the reaction. For example, alkali metal hydroxides such as sodium hydroxide and potassium hydroxide, alkali metal carbonates such as sodium carbonate and potassium carbonate, organic bases such as pyridine, or mixtures thereof, are used as the acid binder. Specifically, when the hydroxyaryl-terminated polydiorganosiloxane (II) used or a part of the dihydric phenol (I) as described above is added to this reaction stage as a post-added monomer, it is preferable to use 2 equivalents or more of alkali relative to the total mole number of the post-added dihydric phenol (I) and the hydroxyaryl-terminated polydiorganosiloxane (II) (usually 1 mole corresponds to 2 equivalents).

[0049] The polycondensation by the interfacial polycondensation reaction between the oligomer of the dihydric phenol (I) and the hydroxyaryl-terminated polydiorganosiloxane (II) is carried out by vigorously stirring the above mixture.

[0050] In such a polymerization reaction, a terminal terminator or a molecular weight regulator is usually used. Examples of the terminal terminator include compounds having a monovalent phenolic hydroxyl group, such as ordinary phenol, p-tert-butylphenol, p-cumylphenol, tribromophenol, etc., as well as long-chain alkylphenols, aliphatic carboxylic acid chlorides, aliphatic carboxylic acids, hydroxybenzoic acid alkyl esters, hydroxyphenyl alkyl acid esters, and alkyl ether phenols. The amount of the terminal terminator is in the range of 100 to 0.5 mol, preferably 50 to 2 mol, relative to 100 mol of all dihydric phenol compounds used, and it is naturally possible to use two or more compounds in combination.

[0051] To accelerate the polycondensation reaction, a catalyst such as a tertiary amine, such as triethylamine, or a quaternary ammonium salt may be added. The reaction time of such a polymerization reaction is preferably 30 minutes or more, more preferably 50 minutes or more. If desired, a small amount of an antioxidant such as sodium sulfite or hydrosulfide may be added.

[0052] A branching agent can be used in combination with the above dihydric phenol compound to produce a branched polycarbonate-polydiorganosiloxane. Examples of polyfunctional aromatic compounds having three or more functional groups that can be used in such branched polycarbonate-polydiorganosiloxane copolymer resins include phloroglucin, phloroglucide, 4,6-dimethyl-2,4,6-tris(4-hydroxyphenyl)heptene-2,2,4,6-trimethyl-2,4,6-tris(4-hydroxyphenyl)heptane, 1,3,5-tris(4-hydroxyphenyl)benzene, 1,1,1-tris(4-hydroxyphenyl)ethane, 1,1,1-tris(3,5-dimethyl-4-hydroxyphenyl)ethane, 2,6-bis(2-hydroxy-5-methylbenzyl)-4-methylphenol, 4-{4-[1 Examples of the hydroxyphenyl ether include trisphenols such as {α,α-dimethylbenzylphenol}-α-dimethylbenzylphenol, tetra(4-hydroxyphenyl)methane, bis(2,4-dihydroxyphenyl)ketone, 1,4-bis(4,4-dihydroxytriphenylmethyl)benzene, trimellitic acid, pyromellitic acid, benzophenonetetracarboxylic acid, and acid chlorides thereof. Among these, 1,1,1-tris(4-hydroxyphenyl)ethane and 1,1,1-tris(3,5-dimethyl-4-hydroxyphenyl)ethane are preferred, and 1,1,1-tris(4-hydroxyphenyl)ethane is particularly preferred. The proportion of the polyfunctional compound in the branched polycarbonate-polydiorganosiloxane copolymer resin is preferably 0.001 to 1 mol %, more preferably 0.005 to 0.9 mol %, further preferably 0.01 to 0.8 mol %, and particularly preferably 0.05 to 0.4 mol %, based on the total amount of the polycarbonate-polydiorganosiloxane copolymer resin. 1 It can be calculated by H-NMR measurement.

[0053] The reaction pressure may be reduced, normal, or increased, but is usually preferably normal pressure or the reaction system's own pressure. The reaction temperature is selected from the range of -20 to 50°C, and in many cases, since heat is generated during polymerization, it is desirable to cool the reaction system with water or ice. The reaction time varies depending on other conditions such as the reaction temperature and cannot be generally specified, but is usually carried out for 0.5 to 10 hours.

[0054] In some cases, the obtained polycarbonate-polydiorganosiloxane copolymer resin is subjected to a suitable physical treatment (mixing, fractionation, etc.) and / or chemical treatment (polymer reaction, crosslinking treatment, partial decomposition treatment, etc.) to obtain a desired reduced viscosity [η SP It can also be obtained as a polycarbonate-polydiorganosiloxane copolymer resin of formula [1 / c].

[0055] The resulting reaction product (crude product) can be subjected to various post-treatments such as known separation and purification methods to recover a polycarbonate-polydiorganosiloxane copolymer resin of a desired purity (degree of purification).

[0056] The average size of the polydiorganosiloxane domains in the polycarbonate-polydiorganosiloxane copolymer resin molded article is preferably in the range of 1 to 40 nm. Such an average size is more preferably 1 to 30 nm, and further preferably 5 to 25 nm. If it is below the lower limit of this preferred range, impact resistance and flame retardancy may not be sufficiently exhibited, and if it exceeds the upper limit of this preferred range, impact resistance may not be stably exhibited.

[0057] The average domain size and normalized dispersion of the polydiorganosiloxane domains of the polycarbonate-polydiorganosiloxane copolymer resin molded product of the present invention were evaluated by small angle X-ray scattering (SAXS). Small angle X-ray scattering is a method for measuring diffuse scattering and diffraction occurring in a small angle region within a scattering angle (2θ) of <10°. In this small angle X-ray scattering method, if there are regions with different electron densities of about 1 to 100 nm in a substance, the diffuse scattering of X-rays is measured based on the electron density difference. The particle size of the measurement object is determined based on the scattering angle and scattering intensity. In the case of a polycarbonate-polydiorganosiloxane copolymer resin that has an aggregate structure in which polydiorganosiloxane domains are dispersed in a polycarbonate polymer matrix, the electron density difference between the polycarbonate matrix and the polydiorganosiloxane domains causes diffuse scattering of X-rays. The scattering intensity I at each scattering angle (2θ) in the range of scattering angles (2θ) less than 10° is measured to measure the small-angle X-ray scattering profile, and assuming that the polydiorganosiloxane domains are spherical domains and that there is variation in the particle size distribution, a simulation is performed using commercially available analysis software from a tentative particle size and a tentative particle size distribution model to determine the average size and particle size distribution (normalized variance) of the polydiorganosiloxane domains. The small-angle X-ray scattering method makes it possible to accurately, easily, and reproducibly measure the average size and particle size distribution of the polydiorganosiloxane domains dispersed in the matrix of a polycarbonate polymer, which cannot be accurately measured by observation with a transmission electron microscope. The average domain size means the number average of the individual domain sizes. The normalized variance means a parameter that normalizes the spread of the particle size distribution by the average size. Specifically, it is a value obtained by normalizing the variance of the polydiorganosiloxane domain size by the average domain size, and is expressed by the following formula (1).

[0058]

number

[0059] The terms "average domain size" and "normalized dispersion" used in connection with the present invention indicate measured values obtained by measuring the 1.0 mm thick portion of the three-layer plate prepared by the method described in the examples by such a small-angle X-ray scattering method. Further, analysis was performed using an isolated particle model that does not consider the particle-particle interaction (particle-particle interference).

[0060] <A - 2 component: ABS resin> The ABS resin used as the A-2 component of the present invention is a copolymer obtained by graft-polymerizing acrylonitrile and styrene to polybutadiene. As the styrene, styrene and α-methylstyrene can be preferably used. The ratio of the component grafted to the polybutadiene is preferably 95 to 20% by weight, more preferably 90 to 50% by weight, based on 100% by weight of the ABS resin component. Furthermore, it is preferable that the acrylonitrile is 5 to 50% by weight and the styrene is 95 to 50% by weight, based on 100% by weight of the total amount of the acrylonitrile and styrene. Furthermore, methyl (meth)acrylate, ethyl acrylate, maleic anhydride, N-substituted maleimide, etc. can be mixed and used as a part of the component graft-polymerized to the polybutadiene, and the content ratio of these is preferably 15% by weight or less in the ABS resin component. Furthermore, various conventionally known initiators, chain transfer agents, emulsifiers, etc. used in the reaction can be used as necessary. In the ABS resin of the present invention, the particle size of the polybutadiene is preferably 0.1 to 5.0 μm, more preferably 0.2 to 3.0 μm, and even more preferably 0.3 to 1.5 μm. The particle size distribution of the polybutadiene may be either a single distribution or a distribution having two or more peaks. Furthermore, the morphology may be either a single phase of the particles or a salami structure formed by containing an occluded phase around the particles. It has been well known that ABS resins contain copolymers of acrylonitrile and styrene that are not grafted to a diene rubber component, and the ABS resin of the present invention may also contain free polymer components generated during such polymerization. The reduced viscosity (30° C.) of such a copolymer of free acrylonitrile and styrene is preferably 0.2 to 1.0 dl / g, more preferably 0.3 to 0.7 dl / g. The ratio of grafted acrylonitrile and styrene to polybutadiene is preferably 20 to 200%, more preferably 20 to 70%, in terms of graft ratio (weight %). Such ABS resin may be produced by any of bulk polymerization, suspension polymerization, and emulsion polymerization, with bulk polymerization being particularly preferred.In the case of bulk polymerization, since it substantially does not contain alkali metal salts and the like derived from emulsifiers and the like, it becomes possible to maintain better thermal stability of the thermoplastic resin composition. Also, the copolymerization method may be one-stage copolymerization or multi-stage copolymerization. Further, a blend obtained by separately copolymerizing acrylonitrile and styrene with the ABS resin obtained by such a production method can also be preferably used.

[0061] <A-3 component: Polyester resin excluding B component> The polyester resin excluding the B component used as the A-3 component of the present invention is preferably a polyester resin in which 70 mol% or more, more preferably 90 mol% or more, and still more preferably 99 mol% or more of 100 mol% of the dicarboxylic acid component forming the polyester resin is an aromatic dicarboxylic acid.

[0062] Examples of this dicarboxylic acid include terephthalic acid, isophthalic acid, 2-chloroterephthalic acid, 2,5-dichloroterephthalic acid, 2-methylterephthalic acid, 4,4-stilbenedicarboxylic acid, 4,4-biphenyldicarboxylic acid, orthophthalic acid, 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, bisbenzoic acid, bis(p-carboxyphenyl)methane, anthracenedicarboxylic acid, 4,4-diphenyletherdicarboxylic acid, 4,4-diphenoxyethanedicarboxylic acid, 5-Na sulfoisophthalic acid, ethylene-bis-p-benzoic acid, and the like. These dicarboxylic acids can be used alone or in combination of two or more. In the polyester resin of the present invention, an aliphatic dicarboxylic acid component of less than 30 mol% can be copolymerized in addition to the above aromatic dicarboxylic acids. Specific examples thereof include adipic acid, sebacic acid, azelaic acid, dodecanedioic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, and the like.

[0063] Examples of the diol component of the present invention include ethylene glycol, diethylene glycol, 1,2-propylene glycol, 1,3-propanediol, 2,2-dimethyl-1,3-propanediol, trans- or cis-2,2,4,4-tetramethyl-1,3-cyclobutanediol, 1,4-butanediol, neopentyl glycol, 1,5-pentanediol, 1,6-hexanediol, 1,4-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, decamethylene glycol, cyclohexanediol, p-xylenediol, bisphenol A, tetrabromobisphenol A, and tetrabromobisphenol A-bis(2-hydroxyethyl ether). These can be used alone or in combination of two or more. The dihydric phenol in the diol component is preferably 30 mol% or less.

[0064] Specific examples of polyester resins include polyethylene terephthalate (PET), polypropylene terephthalate, polybutylene terephthalate (PBT), polyhexylene terephthalate, polyethylene naphthalate (PEN), polybutylene naphthalate (PBN), polyethylene-1,2-bis(phenoxy)ethane-4,4'-dicarboxylate, and the like, as well as copolymer polyester resins such as polyethylene isophthalate / terephthalate copolymers and polybutylene terephthalate / isophthalate copolymers.

[0065] The end group structure of the polyester resin used in the present invention is not particularly limited, and the ratio of hydroxyl groups and carboxyl groups in the end groups may be approximately equal, or one of them may be more than the other. Furthermore, the end groups may be blocked by reacting with a compound having reactivity with the end groups.

[0066] The method for producing the polyester resin used in the present invention is carried out by polymerizing the dicarboxylic acid component and the diol component while heating in the presence of a polycondensation catalyst containing titanium, germanium, antimony, etc., according to a conventional method, and discharging the by-product water or lower alcohol out of the system. For example, germanium-based polymerization catalysts include germanium oxides, hydroxides, halides, alcoholates, phenolates, etc., and more specifically, germanium oxide, germanium hydroxide, germanium tetrachloride, tetramethoxygermanium, etc. can be exemplified. In the present invention, compounds such as manganese, zinc, calcium, magnesium, etc., which are used in the transesterification reaction, which is a step before polycondensation, can be used in combination, and after the transesterification reaction, such catalysts can be deactivated by a phosphoric acid or phosphorous acid compound, etc., to perform polycondensation. Furthermore, the method for producing the polyester resin can be either a batch method or a continuous polymerization method.

[0067] Among the above polyester resins, polyethylene terephthalate is particularly suitable. The polyethylene terephthalate of the present invention is a polymer obtained by polycondensation reaction of terephthalic acid or a derivative thereof with 1,4-ethanediol or a derivative thereof, and includes copolymers of other dicarboxylic acid components and other alkylene glycol components as described above.

[0068] The end group structure of polyethylene terephthalate is not particularly limited as described above, but those with fewer terminal carboxyl groups compared to terminal hydroxyl groups are more preferred. Also, regarding the production method, the above various methods can be adopted, but a continuous polymerization type is preferred. This is because its quality stability is high and it is also cost-effective. Furthermore, it is preferable to use an organic titanium compound as the polymerization catalyst. This is because it tends to have less influence on transesterification reactions and the like. Specific preferred examples of such organic titanium compounds include titanium tetrabutoxide, titanium isopropoxide, titanium oxalate, titanium acetate, titanium benzoate, titanium trimellitate, and the reaction product of tetrabutyl titanate and trimellitic anhydride. The usage amount of the organic titanium compound is preferably in a ratio such that the titanium atom is 3 to 12 mg atoms% relative to the acid component constituting polyethylene terephthalate.

[0069] The molecular weight of the polyester resin of the present invention is not particularly limited, but the intrinsic viscosity measured at 35 °C using o-chlorophenol as a solvent is preferably 0.5 to 1.5, more preferably 0.6 to 1.2.

[0070] <A-4 component: AS resin> The AS resin used as the A-4 component of the present invention is a copolymer of acrylonitrile and styrene. The AS resin may have high stereoregularity such as syndiotactic polystyrene by using a catalyst such as a metallocene catalyst during its production. Further, in some cases, polymers and copolymers with a narrow molecular weight distribution, block copolymers, and polymers and copolymers with high stereoregularity obtained by methods such as anionic living polymerization and radical living polymerization can also be used.

[0071] <A-5 component: PS resin> The PS resin used as the A-5 component of the present invention is a polymer of styrene.

[0072] <A-6 component: AAS resin> The AAS resin used as the A-6 component of the present invention is a copolymer composed of acrylonitrile, styrene, and an acrylic rubber component.

[0073] <Component B: Fatty acid polyester resin> The thermoplastic resin composition of the present invention contains, as component B, a fatty acid polyester resin containing a structural unit derived from at least one alcohol selected from the group consisting of 1-docosanol and 1-octacosanol. When a fatty acid polyester resin other than the above is used as component B, the recyclability (release load) deteriorates.

[0074] The content of the above structural unit is preferably 30 mol% or more, more preferably 40 mol% or more, of all the structural units derived from the alcohol in the fatty acid polyester resin. The upper limit of the content of the above structural unit is preferably 70 mol% or less, more preferably 60 mol% or less.

[0075] The acid value of component B is preferably 50 mgKOH / g or less, more preferably 10 mgKOH / g or less. When the acid value exceeds 50 mgKOH / g, the strength retention rate and recyclability after retention may deteriorate. The lower limit of the acid value is not particularly limited, but it is preferably 1 mgKOH / g or more.

[0076] The content of component B is 0.01 to 1 part by weight, preferably 0.05 to 0.9 part by weight, more preferably 0.1 to 0.5 part by weight, based on 100 parts by weight of component A. When the content of component B is less than 0.01 part by weight, the release property deteriorates, and when it exceeds 1 part by weight, the recyclability deteriorates.

[0077] <Component C: Phosphate ester> The thermoplastic resin composition of the present invention contains at least one phosphate ester selected from the group consisting of a phosphonic acid ester (C-1 component) having an acid value of 0.01 to 0.30 mgKOH / g, an acidic phosphate ester (C-2 component) having an acid value of 10 to 200 mgKOH / g, and a trialkyl phosphate (C-3 component). The content of the C component is 0.001 to 1 part by weight, preferably 0.01 to 0.1 part by weight, more preferably 0.01 to 0.07 part by weight, based on 100 parts by weight of the A component. When the content of the C component is less than 0.001 part by weight or exceeds 1 part by weight, the strength reduction during molding is significant and the recyclability also deteriorates.

[0078] <C-1 component: phosphonic acid ester> As the phosphonic acid ester used in the present invention, phosphonic acid monoester, phosphonic acid diester, and phosphonic acid triester can be used, but phosphonic acid triester is preferred. Various combinations of esters with carbon numbers from 1 to 22 can be used, but triethyl phosphonoacetate is most preferred. The acid value of the phosphonic acid ester is 0.01 to 0.30 mgKOH / g, preferably 0.01 to 0.20 mgKOH / g, more preferably 0.05 to 0.15 mgKOH / g. Those with an acid value less than 0.01 mgKOH / g are not practical in production, and when it is greater than 0.30 mgKOH / g, the strength reduction during molding is significant and the recyclability also deteriorates. The acid value was measured using a potentiometric titration apparatus, and an alcohol solution of the phosphonic acid ester was titrated with a KOH alcohol solution.

[0079] <C-2 component: acidic phosphate ester> The acidic phosphate esters used in the present invention may be monoester phosphates, diester phosphates, triester phosphates, and mixtures thereof, with a mixture of monoester and diester being preferred. Various combinations of esters with 1 to 22 carbon atoms can be used, but stearyl acid phosphate is most preferred. The acid value of the acidic phosphate ester is 10 to 200 mgKOH / g, preferably 120 to 180 mgKOH / g, more preferably 150 to 170 mgKOH / g. When the acid value is less than 10 mgKOH / g, it is not practical for production as an acidic phosphate ester, and when the acid value is greater than 200 mgKOH / g, the strength during molding processing decreases significantly and the recyclability also deteriorates. The acid value was measured using a potentiometric titration apparatus, and an alcohol solution of the acidic phosphate ester was titrated with a KOH alcohol solution.

[0080] <C-3 component: Trialkyl phosphate> Examples of the trialkyl phosphates used in the present invention include tributyl phosphate, triisopropyl phosphate, triethyl phosphate, and trimethyl phosphate, etc., with trimethyl phosphate being preferred.

[0081] (Other additives) For the improvement of the thermal stability and designability of the thermoplastic resin composition of the present invention, additives used for these improvements are advantageously used. These additives will be specifically described below.

[0082] (I) Heat stabilizer The thermoplastic resin composition of the present invention can be blended with various known stabilizers other than component C. Examples of the stabilizer include hindered phenol antioxidants.

[0083] (i) Hindered phenol antioxidant The thermoplastic resin composition of the present invention may contain a hindered phenol-based antioxidant. Such incorporation exerts an effect of suppressing deterioration of color during molding processing and deterioration of color over a long period of use. Examples of the hindered phenol-based antioxidant include α-tocopherol, butyl hydroxytoluene, sinapyl alcohol, vitamin E, n-octadecyl-β-(4'-hydroxy-3',5'-di-tert-butylphenyl)propionate, 2-tert-butyl-6-(3'-tert-butyl-5'-methyl-2'-hydroxybenzyl)-4-methylphenyl acrylate, 2,6-di-tert-butyl-4-(N,N-dimethylaminomethyl)phenol, 3,5 -Di-tert-butyl-4-hydroxybenzylphosphonate diethyl ester, 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 2,2'-methylenebis(4-ethyl-6-tert-butylphenol), 4,4'-methylenebis(2,6-di-tert-butylphenol), 2,2'-methylenebis(4-methyl-6-cyclohexylphenol), 2,2'-dimethylene-bis(6-α-methyl-benzyl-p-cresol) 2,2'-ethyl 2,2'-butylidene-bis(4-methyl-6-tert-butylphenol), 4,4'-butylidenebis(3-methyl-6-tert-butylphenol), triethylene glycol-N-bis-3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate, 1,6-hexanediol bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], bis[2-te rt-Butyl-4-methyl 6-(3-tert-butyl-5-methyl-2-hydroxybenzyl)phenyl] terephthalate, 3,9-bis{2-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1,-dimethylethyl}-2,4,8,10-tetraoxaspiro[5,5]undecane, 4,4'-thiobis(6-tert-butyl-m-cresol), 4,4'-thiobis(3-methyl-6-tert-butylphenol), 2,2'-thiobis(4-methyl-6-tert-butylphenol), bis(3,5-di-tert-butyl-4-hydroxybenzyl)sulfide, 4,4'-dithiobis(2,6-di-tert-butylphenol), 4,4'-trithiobis(2,6-di-tert-butylphenol), 2,2-thiodiethylene bis-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 2,4-bis(n-octylthio)-6-(4-hydroxy-3',5'-di-tert-butylanilino)-1,3,5-triazine, N,N'-hexamethylene bis-(3,5-di-tert-butyl-4-hydroxyhydrocinnamide), N,N'-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine, 1,1 Examples include 1,3,5-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, tris(3,5-di-tert-butyl-4-hydroxyphenyl)isocyanurate, tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanurate, 1,3,5-tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl)isocyanurate, 1,3,5-tris2[3(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxy]ethyl isocyanurate, and tetrakis[methylene-3-(3',5'-di-tert-butyl-4-hydroxyphenyl)propionate]methane. All of these are readily available. The above hindered phenol-based antioxidants can be used alone or in combination of two or more. The content of the hindered phenol-based antioxidant is preferably 0.0001 to 1 part by weight, more preferably 0.001 to 0.5 parts by weight, and even more preferably 0.005 to 0.3 parts by weight, based on 100 parts by weight of component A.

[0084] (ii) Heat stabilizers other than hindered phenol antioxidants The thermoplastic resin composition of the present invention may also contain other heat stabilizers than the C component and the hindered phenol-based antioxidant. Suitable examples of such other heat stabilizers include lactone-based stabilizers such as the reaction product of 3-hydroxy-5,7-di-tert-butyl-furan-2-one and o-xylene. Details of such stabilizers are described in JP-A-7-233160. Such a compound is commercially available as Irganox HP-136 (trademark, manufactured by CIBA SPECIALTY CHEMICALS), and this compound can be used. Furthermore, stabilizers in which this compound is mixed with various phosphite compounds and hindered phenol compounds are commercially available. Suitable examples include Irganox HP-2921 manufactured by the same company. The content of the lactone-based stabilizer is preferably 0.0005 to 0.05 parts by weight, more preferably 0.001 to 0.03 parts by weight, based on 100 parts by weight of the A component. Other examples of the stabilizer include sulfur-containing stabilizers such as pentaerythritol tetrakis (3-mercaptopropionate), pentaerythritol tetrakis (3-laurylthiopropionate), and glycerol-3-stearylthiopropionate. The content of such sulfur-containing stabilizers is preferably 0.001 to 0.1 parts by weight, more preferably 0.01 to 0.08 parts by weight, based on 100 parts by weight of component A. An epoxy compound can be blended into the thermoplastic resin composition of the present invention as necessary. Such an epoxy compound is blended for the purpose of suppressing mold corrosion, and basically all compounds having an epoxy functional group can be applied. Specific examples of preferred epoxy compounds include 3,4-epoxycyclohexylmethyl-3',4'-epoxycyclohexylcarboxylate, 1,2-epoxy-4-(2-oxiranyl)cyclohexane adduct of 2,2-bis(hydroxymethyl)-1-butanol, a copolymer of methyl methacrylate and glycidyl methacrylate, a copolymer of styrene and glycidyl methacrylate, etc. The content of such epoxy compounds is preferably 0.003 to 0.2 parts by weight, more preferably 0.004 to 0.15 parts by weight, and even more preferably 0.005 to 0.1 parts by weight, relative to 100 parts by weight of component A.

[0085] (II) Anti-drip agent As the drip prevention agent, a fibrillation type fluoropolymer is preferably used, and polytetrafluoroethylene (fibrillated PTFE) is particularly preferred. The fibrillated PTFE may be fibrillated PTFE alone or may be a mixed form of fibrillated PTFE, i.e., a polytetrafluoroethylene mixture consisting of fibrillated PTFE particles and an organic polymer. The fibrillated PTFE has an extremely high molecular weight, and tends to bond PTFE to each other to form a fiber by an external action such as a shear force. The number average molecular weight is in the range of 1.5 million to tens of millions. The lower limit is more preferably 3 million. The number average molecular weight is calculated based on the melt viscosity of polytetrafluoroethylene at 380°C, as disclosed in, for example, JP-A-6-145520. That is, the fibrillated PTFE has a melt viscosity at 380°C of 10 7 ~10 13 The range is preferably 10 8 ~10 12 The range of poise. Such fibrillated PTFE can be used in the form of an aqueous dispersion in addition to a solid form. In addition, such fibrillated PTFE can be used in the form of a PTFE mixture mixed with other resins to improve dispersibility in resins and obtain better flame retardancy and mechanical properties.

[0086] Furthermore, as disclosed in Japanese Patent Application Laid-Open No. 6-145520, a structure having such fibrillated PTFE as a core and low molecular weight polytetrafluoroethylene as a shell is also preferably used.

[0087] Examples of commercially available products of such fibrillated PTFE include Teflon (registered trademark) 6J from Mitsui DuPont Fluorochemicals Co., Ltd., and Polyflon MPA FA500 and F-201L from Daikin Chemical Industries, Ltd.

[0088] The mixed form of fibrillated PTFE can be prepared by (1) mixing an aqueous dispersion of fibrillated PTFE with an aqueous dispersion or solution of an organic polymer and co-precipitating to obtain a coagulated mixture (methods described in JP-A-60-258263, JP-A-63-154744, etc.), (2) mixing an aqueous dispersion of fibrillated PTFE with dried organic polymer particles (method described in JP-A-4-272957), or (3) uniformly mixing an aqueous dispersion of fibrillated PTFE with a solution of organic polymer particles and extracting the fibrillated PTFE from the mixture. (4) a method of simultaneously removing the media from the fibrillated PTFE and the organic polymer in an aqueous dispersion of fibrillated PTFE (method described in JP-A-06-220210, JP-A-08-188653, etc.), (5) a method of uniformly mixing an aqueous dispersion of PTFE and an organic polymer dispersion, and then polymerizing a vinyl monomer in the mixed dispersion to obtain a mixture (method described in JP-A-11-29679, etc.).

[0089] Commercially available products of these mixed forms of fibrillated PTFE include the Metablen A series represented by "Metablen A3000" (product name), "Metablen A3700" (product name), and "Metablen A3800" (product name) manufactured by Mitsubishi Rayon Co., Ltd., SN3300B7 (product name) manufactured by Shine Polymer, and "BLENDEX B449" (product name) manufactured by GE Specialty Chemicals.

[0090] The ratio of fibrillated PTFE in the mixed form is preferably 1 wt% to 95 wt%, more preferably 10 wt% to 90 wt%, and most preferably 20 wt% to 80 wt%, of 100 wt% of the mixture.

[0091] When the ratio of fibrillated PTFE in the mixed form is within this range, good dispersibility of the fibrillated PTFE can be achieved. The content of fibrillated PTFE is preferably 0.005 to 20 parts by weight, more preferably 0.01 to 0.5 parts by weight, and even more preferably 0.1 to 0.5 parts by weight, relative to 100 parts by weight of component A. If the content is less than 0.005 parts by weight, it is difficult to obtain a flame retardant effect, and if it exceeds 20 parts by weight, the thermal shock resistance (electromagnetic shielding properties) may decrease.

[0092] (III) Dyes and pigments The thermoplastic resin composition of the present invention further contains various dyes and pigments, and can provide molded products that exhibit a variety of designs. Examples of dyes and pigments used in the present invention include perylene dyes, coumarin dyes, thioindigo dyes, anthraquinone dyes, thioxanthone dyes, ferrocyanides such as Prussian blue, perinone dyes, quinoline dyes, quinacridone dyes, dioxazine dyes, isoindolinone dyes, and phthalocyanine dyes. Furthermore, the thermoplastic resin composition of the present invention can be blended with a metallic pigment to obtain a better metallic color. Aluminum powder is suitable as the metallic pigment. In addition, by blending a fluorescent brightener or other fluorescent dye that emits light, a better design effect that makes use of the luminous color can be imparted.

[0093] (IV) Fluorescent whitening agents In the thermoplastic resin composition of the present invention, the fluorescent brightener is not particularly limited as long as it is used to improve the color tone of the resin or the like to white or bluish white, and examples thereof include stilbene-based, benzimidazole-based, benzoxazole-based, naphthalimide-based, rhodamine-based, coumarin-based, and oxazine-based compounds. Specific examples include CI Fluorescent Brightener 219:1, Eastman Chemical Company's EASTOBRITE OB-1, and Showa Chemical Company's "HAKKOL PSR." Here, the fluorescent brightener has the effect of absorbing ultraviolet energy of light and radiating this energy in the visible region. The content of the fluorescent brightener is preferably 0.001 to 0.1 parts by weight, more preferably 0.001 to 0.05 parts by weight, based on 100 parts by weight of the A component. Even if the content exceeds 0.1 parts by weight, the effect of improving the color tone of the composition may be small.

[0094] (V) Compounds capable of absorbing heat rays The thermoplastic resin composition of the present invention may contain a compound having heat absorbing ability. Suitable examples of such compounds include phthalocyanine-based near infrared absorbing agents, metal oxide-based near infrared absorbing agents such as ATO, ITO, iridium oxide, ruthenium oxide, immonium oxide, and titanium oxide, various metal compounds having excellent near infrared absorbing ability such as metal boride-based and tungsten oxide-based near infrared absorbing agents such as lanthanum boride, cerium boride, and tungsten boride, and carbon fillers. As such phthalocyanine-based near infrared absorbing agents, for example, MIR-362 manufactured by Mitsui Chemicals, Inc. is commercially available and easily available. Examples of carbon fillers include carbon black, graphite (both natural and artificial), and fullerene, and preferably carbon black and graphite. These can be used alone or in combination of two or more. The content of the phthalocyanine-based near infrared absorbing agent is preferably 0.0005 to 0.2 parts by weight, more preferably 0.0008 to 0.1 parts by weight, and even more preferably 0.001 to 0.07 parts by weight, relative to 100 parts by weight of component A. The contents of the metal oxide-based near infrared absorbing agent, metal boride-based near infrared absorbing agent, and carbon filler are preferably in the range of 0.1 to 200 ppm (weight ratio), and more preferably in the range of 0.5 to 100 ppm, in the thermoplastic resin composition of the present invention.

[0095] (VI) Light diffusing agent The thermoplastic resin composition of the present invention can be blended with a light diffusing agent to impart a light diffusing effect. Examples of such light diffusing agents include polymer fine particles, inorganic fine particles with a low refractive index such as calcium carbonate, and composites thereof. Such polymer fine particles are fine particles already known as light diffusing agents for thermoplastic resins. More preferred examples include acrylic crosslinked particles with a particle size of several μm and silicone crosslinked particles represented by polyorganosilsesquioxane. Examples of the shape of the light diffusing agent include spherical, discoid, columnar, and amorphous shapes. Such a sphere does not need to be a perfect sphere and includes deformed ones, and such a columnar shape includes a cube. A preferred light diffusing agent is spherical, and the more uniform the particle size, the more preferred it is. The content of the light diffusing agent is preferably 0.005 to 20 parts by weight, more preferably 0.01 to 10 parts by weight, and even more preferably 0.01 to 3 parts by weight, relative to 100 parts by weight of component A. Two or more types of light diffusing agents can be used in combination.

[0096] (VII) Highly light-reflecting white pigments The thermoplastic resin composition of the present invention can be blended with a highly light-reflective white pigment to impart a light-reflecting effect. Titanium dioxide (particularly titanium dioxide treated with an organic surface treatment agent such as silicone) pigment is particularly preferred as such a white pigment. The content of such highly light-reflective white pigment is preferably 3 to 30 parts by weight, more preferably 8 to 25 parts by weight, per 100 parts by weight of component A. Two or more types of highly light-reflective white pigments can be used in combination.

[0097] (VIII) Ultraviolet absorbers The thermoplastic resin composition of the present invention can be blended with an ultraviolet absorbing agent to impart weather resistance.Specific examples of such ultraviolet absorbing agents include benzophenone-based agents such as 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-octoxybenzophenone, 2-hydroxy-4-benzyloxybenzophenone, 2-hydroxy-4-methoxy-5-sulfoxybenzophenone, 2,2'-dihydroxy-4-methoxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxy-5-sodiumsulfoxybenzophenone, bis(5-benzoyl-4-hydroxy-2-methoxyphenyl)methane, 2-hydroxy-4-n-dodecyloxybenzophenone, and 2-hydroxy-4-methoxy-2'-carboxybenzophenone.Specific examples of the ultraviolet absorber include benzotriazole-based ultraviolet absorbers such as 2-(2-hydroxy-5-methylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, 2-(2-hydroxy-3,5-dicumylphenyl)phenylbenzotriazole, 2-(2-hydroxy-3-tert-butyl-5-methylphenyl)-5-chlorobenzotriazole, 2,2'-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol], 2-(2-hydroxy-3,5-di-tert-butylphenyl)benzotriazole, 2-(2-hydroxy-3,5-di-tert-butylphenyl)-5-chlorobenzotriazole, 2-(2-hydroxy-3,5-di-tert-amylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, Examples of the copolymer include 2-hydroxyphenyl-2H-benzotriazole skeleton such as 2-(2-hydroxy-5-acryloxyethylphenyl)-2H-benzotriazole, 2-(2-hydroxy-5-tert-butylphenyl)-benzotriazole, 2-(2-hydroxy-4-octoxyphenyl)-benzotriazole, 2,2'-methylenebis(4-cumyl-6-benzotriazolephenyl), 2,2'-p-phenylenebis(1,3-benzoxazin-4-one), and 2-[2-hydroxy-3-(3,4,5,6-tetrahydrophthalimidomethyl)-5-methylphenyl]benzotriazole, and copolymers of 2-(2'-hydroxy-5-methacryloxyethylphenyl)-2H-benzotriazole and vinyl monomers copolymerizable with the monomer, and copolymers of 2-(2'-hydroxy-5-acryloxyethylphenyl)-2H-benzotriazole and vinyl monomers copolymerizable with the monomer.Specific examples of the ultraviolet absorber include, in the hydroxyphenyltriazine series, 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-hexyloxyphenol, 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-methyloxyphenol, 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-ethyloxyphenol, 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-propyloxyphenol, and 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-butyloxyphenol.Further examples include compounds in which the phenyl group of the above-mentioned compounds is a 2,4-dimethylphenyl group, such as 2-(4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2-yl)-5-hexyloxyphenol. Specific examples of the ultraviolet absorbent include cyclic iminoesters such as 2,2'-p-phenylenebis(3,1-benzoxazine-4-one), 2,2'-m-phenylenebis(3,1-benzoxazine-4-one), and 2,2'-p,p'-diphenylenebis(3,1-benzoxazine-4-one). Specific examples of the ultraviolet absorbent include cyanoacrylates such as 1,3-bis-[(2'-cyano-3',3'-diphenylacryloyl)oxy]-2,2-bis[(2-cyano-3,3-diphenylacryloyl)oxy]methyl)propane and 1,3-bis-[(2-cyano-3,3-diphenylacryloyl)oxy]benzene. Furthermore, the ultraviolet absorber may be a polymer type ultraviolet absorber obtained by copolymerizing such an ultraviolet absorbing monomer and / or a light stable monomer with a monomer such as an alkyl (meth)acrylate by adopting a structure of a radically polymerizable monomer compound. Suitable examples of the ultraviolet absorbing monomer include compounds containing a benzotriazole skeleton, a benzophenone skeleton, a triazine skeleton, a cyclic imino ester skeleton, and a cyanoacrylate skeleton in the ester substituent of a (meth)acrylic acid ester.Among the above, benzotriazole and hydroxyphenyltriazine are preferred in terms of ultraviolet absorbing ability, and cyclic iminoester and cyanoacrylate are preferred in terms of heat resistance and color. Specific examples include "Chemisorb 79" from Chemipro Chemical Co., Ltd. and "Tinuvin 234" from BASF Japan Ltd. The ultraviolet absorbing agents may be used alone or in a mixture of two or more kinds.

[0098] The content of the ultraviolet absorber is preferably 0.01 to 3 parts by weight, more preferably 0.01 to 1 part by weight, further preferably 0.05 to 1 part by weight, and particularly preferably 0.05 to 0.5 part by weight, relative to 100 parts by weight of the A component.

[0099] (IX) Antistatic agents The thermoplastic resin composition of the present invention may be required to have antistatic properties, and in such a case, it is preferable to include an antistatic agent. Examples of such antistatic agents include (1) organic sulfonate phosphonium salts such as arylsulfonate phosphonium salts, typified by dodecylbenzenesulfonate phosphonium salts, and alkylsulfonate phosphonium salts, as well as borate phosphonium salts such as tetrafluoroborate phosphonium salts. The content of the phosphonium salt is appropriately 5 parts by weight or less, preferably 0.05 to 5 parts by weight, more preferably 1 to 3.5 parts by weight, and even more preferably 1.5 to 3 parts by weight, relative to 100 parts by weight of component A. Examples of antistatic agents include (2) organic sulfonate alkali (earth) metal salts such as lithium organic sulfonate, sodium organic sulfonate, potassium organic sulfonate, cesium organic sulfonate, rubidium organic sulfonate, calcium organic sulfonate, magnesium organic sulfonate, and barium organic sulfonate. As mentioned above, such metal salts are also used as flame retardants. More specifically, such metal salts include metal salts of dodecylbenzenesulfonic acid and metal salts of perfluoroalkanesulfonic acid. The content of the alkali (earth) metal salt of organic sulfonic acid is suitably 0.5 parts by weight or less, preferably 0.001 to 0.3 parts by weight, and more preferably 0.005 to 0.2 parts by weight, per 100 parts by weight of component A. In particular, alkali metal salts such as potassium, cesium, and rubidium are suitable.

[0100] Examples of the antistatic agent include (3) organic ammonium sulfonate salts such as ammonium alkylsulfonate salts and ammonium arylsulfonate salts. The amount of the ammonium salt is preferably 0.05 parts by weight or less per 100 parts by weight of the components consisting of the A component and the B component. Examples of the antistatic agent include (4) polymers containing a poly(oxyalkylene) glycol component as a constituent component, such as polyether ester amide. The amount of the polymer is preferably 5 parts by weight or less per 100 parts by weight of the A component.

[0101] (X) Filler The thermoplastic resin composition of the present invention can be blended with various fillers known as reinforcing fillers. As such fillers, various fibrous fillers, plate-like fillers, and granular fillers can be used. Here, the plate-like fillers are fillers that have a plate-like shape (including those with uneven surfaces and those with curved plates). The granular fillers are fillers with shapes other than those mentioned above, including those with irregular shapes.

[0102] Examples of fibrous fillers include glass fiber, metal-coated glass fiber, and milled glass fiber. The glass fiber that is the base of such fibrous glass fillers is obtained by quenching molten glass while stretching it by various methods to form it into a predetermined fiber shape. The quenching and stretching in such cases are not particularly limited. The cross-sectional shape may be a perfect circle, or a shape other than a perfect circle such as an ellipse, cocoon, flat, or trefoil. Furthermore, a mixture of a perfect circle and a shape other than a perfect circle may be used. The flat shape is a shape in which the average major axis of the fiber cross section is 10 to 50 μm, preferably 15 to 40 μm, and more preferably 20 to 35 μm, and the average ratio of the major axis to the minor axis (major axis / minor axis) is 1.5 to 8, preferably 2 to 6, and more preferably 2.5 to 5.

[0103] In addition, the average fiber diameter of the fibrous glass filler having a high aspect ratio such as glass fiber is preferably 1 to 25 μm, more preferably 3 to 17 μm. When a filler having an average fiber diameter in this range is used, it may be possible to develop good mechanical strength without impairing the appearance of the molded product. In addition, the fiber length of the fibrous glass filler having a high aspect ratio is preferably 60 to 500 μm, more preferably 100 to 400 μm, and particularly preferably 120 to 350 μm, as the number average fiber length in the thermoplastic resin composition. The number average fiber length is a value calculated by an image analyzer from an image obtained by observing the residue of the filler collected by high-temperature incineration of the molded product, dissolution with a solvent, and decomposition with a chemical, etc., using an optical microscope. In addition, when calculating this value, it is a value obtained by a method in which the fiber diameter is used as a guide and lengths less than the fiber diameter are not counted. The aspect ratio of the high aspect ratio fibrous glass filler is preferably 10 to 200, more preferably 15 to 100, and further preferably 20 to 50. The aspect ratio of the filler refers to the value obtained by dividing the average fiber length by the average fiber diameter.

[0104] Milled glass fibers are usually produced by shortening glass fibers using a grinder such as a ball mill. The aspect ratio of a fibrous glass filler having a low aspect ratio such as milled glass fibers is preferably 2 to 10, more preferably 3 to 8. The fiber length of the fibrous glass filler having a low aspect ratio is preferably 5 to 150 μm, more preferably 9 to 80 μm, as the number average fiber length in the thermoplastic resin composition. The average fiber diameter is preferably 1 to 15 μm, more preferably 3 to 13 μm.

[0105] Preferred examples of the plate-like filler include glass flakes, talc, mica, kaolin, metal flakes, carbon flakes, and graphite, as well as plate-like fillers obtained by surface-coating these fillers with different materials such as metals and metal oxides. The particle size is preferably in the range of 0.1 to 300 μm. The particle size refers to the value of the median diameter (D50) of the particle size distribution measured by the X-ray transmission method, which is one of the liquid phase precipitation methods, in the region up to about 10 μm, the value of the median diameter (D50) of the particle size distribution measured by the laser diffraction / scattering method in the region of 10 to 50 μm, and the value of the vibration sieving method in the region of 50 to 300 μm. The particle size is the particle size in the resin composition. The plate-like filler may be surface-treated with various coupling agents such as silane-, titanate-, aluminate-, and zirconate-based coupling agents, or may be in the form of granules that have been bundled or compressed with various resins such as olefin-, styrene-, acrylic-, polyester-, epoxy-, and urethane-based resins, or higher fatty acid esters.

[0106] (XI) Elastomer The thermoplastic resin composition of the present invention may contain a small amount of elastomer within a range that does not impair the effects of the present invention and that allows the effects of the present invention to be exhibited. The amount of elastomer is preferably 20 parts by weight or less, more preferably 10 parts by weight or less, even more preferably 5 parts by weight or less, and most preferably 3 parts by weight or less, based on 100 parts by weight of component A. Examples of elastomers include isobutylene / isoprene rubber, styrene / butadiene rubber, ethylene / propylene rubber, acrylic elastomers, polyester elastomers, polyamide elastomers, and core-shell elastomers such as MBS (methyl methacrylate / styrene / butadiene) rubber, MB (methyl methacrylate / butadiene) rubber, and MAS (methyl methacrylate / acrylonitrile / styrene) rubber.

[0107] (XII) Other Additives The thermoplastic resin composition of the present invention may also contain other flow modifiers, antibacterial agents, dispersants such as liquid paraffin, photocatalytic antifouling agents, photochromic agents, and the like.

[0108] <Production of Resin Composition> The thermoplastic resin composition of the present invention can be pelletized by melt kneading using an extruder such as a single screw extruder or a twin screw extruder. When preparing such pellets, the above-mentioned various reinforcing fillers and additives can also be blended.

[0109] <Regarding the manufacturing of molded products> The thermoplastic resin composition of the present invention can be used to produce various molded products by injection molding the pellets produced as described above. Furthermore, it is also possible to directly produce sheets, films, irregular extrusion molded products, direct blow molded products, and injection molded products from the resin composition melt-kneaded in an extruder without passing through pellets. In such injection molding, molded products can be obtained using injection molding methods such as injection compression molding, injection press molding, gas-assisted injection molding, foam molding (including injection of supercritical fluid), insert molding, in-mold coating molding, heat-insulating mold molding, rapid heating and cooling mold molding, two-color molding, sandwich molding, and ultra-high speed injection molding, in addition to ordinary molding methods, as appropriate for the purpose. The advantages of these various molding methods are already widely known. In addition, either the cold runner method or the hot runner method can be selected for molding. The resin composition of the present invention can also be used in the form of various irregular extrusion molded products, sheets, and films by extrusion molding. In addition, the inflation method, calendar method, casting method, and the like can be used for molding sheets and films. Furthermore, it is also possible to mold the resin composition into a heat-shrinkable tube by subjecting it to a specific stretching operation. The resin composition of the present invention can also be formed into molded articles by rotational molding, blow molding, or the like. Effect of the Invention

[0110] The thermoplastic resin composition of the present invention is a thermoplastic resin composition that exhibits excellent mold releasability, little decrease in strength, and excellent recyclability even under harsh processing conditions. Therefore, the composition is useful in applications requiring thin and lightweight products under high-temperature molding conditions and in cases where products are recycled and reused, and the industrial effects thereof are extremely significant. [Brief description of the drawings]

[0111] [Figure 1] This is a molded product for measuring the demolding load. [Diagram 2] This is a molded product for measuring the demolding load. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0112] The embodiments of the present invention are those that summarize the preferred ranges of the above-mentioned requirements, and representative examples are described in the following examples, although the present invention is not limited to these embodiments. EXAMPLES

[0113] The present invention will be further explained below with reference to examples, but is not limited thereto. The following items were evaluated.

[0114] (i) Demoldability (Mold release load) Pellets obtained from each composition of the examples were dried in a hot air dryer at 100°C for 5 hours, and box-shaped molded products with a width of 100 mm, a length of 150 mm, a height of 30 mm, and a thickness of 2 mm as shown in Figure 1 were continuously molded using an injection molding machine [Sumitomo Heavy Industries, Ltd. SG150U SM IV] under the conditions of the temperature and injection pressure in the table of 100 MPa, and the average value of the demolding load after 10 to 15 shots was measured. The measurement was performed by installing a load cell behind the ejector pin and measuring the maximum load required to demold the box-shaped molded product from the mold. The demolding load must be 180 N or less.

[0115] (ii) Thermal stability (strength retention during retention) The pellets obtained from each composition of the examples were dried in a hot air dryer at 100°C for 5 hours, and 100 shots of 150mm x 150mm x 2mmt square plates were molded continuously at the temperatures in the table using an injection molding machine [Sumitomo Heavy Industries, Ltd. SG150U SM IV]. The operation of the molding machine was then interrupted, and the resin was allowed to remain in the cylinder. After 15 minutes, a square plate was molded again, and a high-speed surface impact test was performed on the square plate before and after the retention, the fracture energy was measured, and the strength retention rate before and after the retention was calculated using the following formula. The measurement was performed using a Hydroshot HTM-1 manufactured by Shimadzu Corporation at 23°C and a test speed of 7m / s. Strength retention rate during dwell (%) = [Fracture energy after dwell / Fracture energy before dwell] x 100 The strength retention rate must be 80% or more.

[0116] (iii) Recyclability (strength retention rate) The square plates used in "(ii) Thermal stability" before storage were left horizontally outdoors in Midori-ku, Chiba City for one year, then crushed and remolded into square plates. The fracture energy of the square plates before storage and the remolded square plates was measured in the same way as in "(ii) Thermal stability", and this fracture energy was taken as the "fracture energy after recycling". The strength retention rate was calculated using the following formula. Strength retention rate after recycling (%) = [Fracture energy after recycling / Fracture energy before leaving] x 100 The strength retention rate after recycling must be 60% or more.

[0117] (iv) Recyclability (rate of increase in release load) The box-shaped molded product used for "(i) Demolding property" was left horizontally outdoors in Midori-ku, Chiba City for one year, then crushed and continuously molded again into a box-shaped molded product. The average demolding load after 10 to 15 molding shots was taken as the "mold release load after recycling," and the increase rate of the demolding load was calculated using the following formula. Increase rate of release load after recycling (%) = [release load after recycling / release load before storage] x 100 The increase in release load after recycling must be 130% or less.

[0118] [Examples 1 to 17, Comparative Examples 1 to 8] Resin compositions having the blending ratios shown in Tables 1 and 2 were prepared as follows. The explanations are given according to the symbols in the tables. Each component in the ratios shown in the tables was weighed and mixed uniformly using a tumbler, and the mixture was fed into an extruder to prepare a resin composition. The extruder used was a vented twin-screw extruder TEX-30XSST (fully intermeshed, rotating in the same direction, two-thread screw) manufactured by Japan Steel Works, Ltd. The extrusion conditions were a discharge rate of 20 kg / h, a screw speed of 150 rpm, and a vent vacuum of 3 kPa, and the extrusion temperature was the temperature shown in the table. Using the obtained pellets, test pieces for evaluation were molded using an injection molding machine according to the above method. The evaluation results are shown in Tables 1 and 2. The components with the symbols in Tables 1 and 2 are as follows:

[0119] (Component A: Thermoplastic resin) A-1-1: Aromatic polycarbonate resin (polycarbonate resin powder with a viscosity average molecular weight of 20,700 made by a conventional method from bisphenol A and phosgene, manufactured by Teijin Ltd., Panlite L-1225WS (product name)) A-1-2: Polycarbonate-polydiorganosiloxane copolymer resin (viscosity average molecular weight 19,800, PDMS content 4.2%, PDMS polymerization degree 37) A-2: ABS resin (Santac AT-07 (product name) manufactured by Nippon A&L Co., Ltd., butadiene rubber component approx. 17.5% by weight, weight average rubber particle diameter 1.2 μm, produced by bulk polymerization) A-3: Polyethylene terephthalate resin (Teijin Ltd., TRN-8550FF (product name)) A-4: AS resin (LiTac A BS-207 (product name) manufactured by Nippon A&L Co., Ltd.) A-5: PS resin (IRPC Public Company Limited, GP-110 (product name)) A-6: AAS resin (777K (product name) manufactured by INEOS)

[0120] (B component: fatty acid polyester resin) B-1: Esters of 1-docosanol and 1-octacosanol with aliphatic carboxylic acids (TOWAX-374, manufactured by Toa Kasei Co., Ltd., acid value 4 mg KOH / g) B-2: Esters of 1-docosanol and 1-octacosanol with aliphatic carboxylic acids (manufactured by Toa Kasei Co., Ltd., X1-220322-1, acid value 66 mg KOH / g) B-3 (Comparative Example): Ester of ethylene glycol and aliphatic carboxylic acid (Licowax E powder, manufactured by Clariant Japan Ltd.) B-4 (Comparative Example): Ester of pentaerythritol and aliphatic carboxylic acid (Rikestar EW-400 (trade name), manufactured by Riken Vitamin Co., Ltd., acid value 9 mg KOH / g)

[0121] (C component) (C-1 component: phosphonic acid ester) C-1-1: Triethyl phosphonoacetate (JC-224 (trade name) manufactured by Johoku Chemical Industry Co., Ltd., acid value 0.08 mg KOH / g) C-1-2 (Comparative Example): Triethyl phosphonoacetate (Solvay, acid value 0.39 mg KOH / g) C-1-3: Triethyl phosphonoacetate (mixture of C-1-1 and C-1-2 (weight ratio 1:1) acid value 0.23 mg KOH / g) (Component C-2: Acid phosphate ester) C-2-1: Stearyl acid phosphate (ADEKA Corporation, AX-71 (trade name), acid value 158 mg KOH / g) C-2-2 (Comparative Example): Stearyl acid phosphate (A-18F (product name), manufactured by SC Organic Chemical Co., Ltd., acid value 215 mg KOH / g) C-2-3: Stearyl acid phosphate (mixture of C-2-1 and C-2-2 (weight ratio 1:1) acid value 187 mg KOH / g) (C-3 component: trialkyl phosphate) C-3-1: Trimethyl phosphate (TMP, manufactured by Daihachi Chemical Industry Co., Ltd.)

[0122] [Table 1]

[0123]

Table 2

Claims

1. A thermoplastic resin composition comprising, per 100 parts by weight of (A) a thermoplastic resin (component A), 0.01 to 1 part by weight of (B) a fatty acid polyester resin (component B) containing a structural unit derived from at least one alcohol selected from the group consisting of 1-docosanol and 1-octacosanol, and (C) 0.001 to 1 part by weight of at least one phosphoric acid ester (component C) selected from the group consisting of a phosphonic acid ester (component C-1) having an acid value of 0.01 to 0.30 mg KOH / g, an acidic phosphoric acid ester (component C-2) having an acid value of 10 to 200 mg KOH / g, and a trialkyl phosphate (component C-3).

2. The thermoplastic resin composition according to claim 1, wherein the component A is at least one thermoplastic resin selected from the group consisting of (A-1) a polycarbonate resin (component A-1), (A-2) an ABS resin (component A-2), (A-3) a polyester resin excluding component B (component A-3), (A-4) an AS resin (component A-4), (A-5) a PS resin (component A-5), and (A-6) an AAS resin (component A-6).

3. 3. The thermoplastic resin composition according to claim 1, wherein the component C is triethylphosphonoacetate.

4. 3. The thermoplastic resin composition according to claim 1, wherein the component C is trimethyl phosphate.

5. 3. The thermoplastic resin composition according to claim 1, wherein the acid value of component B is 50 mgKOH / g or less.

6. A molded article obtained by molding the thermoplastic resin composition according to claim 1 or 2.

Citation Information

Patent Citations

  • JP1974083427A

  • Measuring device of differential pressure

    JP1981040734A